Palladium-Catalyzed Synthesis of Quino[2,3-a]carbazoles and Indolo[2,3-a]carbazoles via Intramolecular ortho-Arylation - Viji, Mayavan; Ghosh, Suman Kr; Nagarajan, Rajagopal (Synthesis, 2014)
An efficient palladium-catalyzed synthesis of quino[2,3-a]carbazoles and indolo[2,3-a]carbazoles from indole-3-acetonitrile via Knoevenagel condensation followed by intramolecular ortho-arylation has been demonstrated.
Keywords: heterocycles; condensation; palladium; arylation